Multiple sclerosis in Colombia and other latin american countries (2013)
The spectrum of multiple sclerosis (MS) in Latin America is characterized by geographic and racial/genetic particularities. In this review we describe major studies of MS epidemiology, genetics, and clinical presentation in Latin America, with a focus on Colombia. We also consider the influence of national health care systems on the treatment of MS in Latin American patients. Epidemiologic studies indicate that the regional incidence of MS in Latin America is more complex than once thought, and broadly consistent with the geographical (latitudinal) distribution of MS in other parts of the world. Low prevalence of MS is considered to be <5/100.000 inhabitants and high prevalence >30/100,000. Colombia is considered a low-risk region for MS, as are other countries located near the equator, such as Panama and Ecuador. By contrast, Latin American countries located farther from the equator are medium or high-risk regions. National health care systems generally cover MS treatment, although bureaucratic problems sometimes interfere with delivery of high-cost medications and access to diagnostic tests, particularly in rural areas. The population of Colombia is racially diverse and genetically heterogeneous, making it difficult to study genetic associations within a complex disease such as MS. The clinical spectrum of MS in Latin America is similar to that of Europe or North America.